PENGARUH PENGGUNAAN VIRGIN COCONUT OIL TERHADAP RUAM POPOK PADA BAYI USIA 0-12 BULAN DI WILAYAH KERJA PUSKESMAS KOTO BESAR TAHUN 2025 - Rati Purwati; Evin Noviana Sari; Niken Suri (Ensiklopedia of Journal, 2025)
Diaper rash is a common problem in infants that can cause discomfort and health problems. Factors that cause diaper rash include friction between the baby's skin and diaper, excessive moisture, bacterial or fungal infections, and poor diaper hygiene. This study aims to determine the effect of using Virgin Coconut Oil (VCO) on diaper rash in infants aged 0-12 months in the working area of Koto Besar Health Center in 2025. This study uses a quantitative method with a posttest only control group design, with 20 respondents divided into two groups: an experimental group (n = 10) given VCO on the diaper rash area, and a control group (n = 10) not given VCO. The sampling technique used is total sampling. The results showed that there was a significant difference between the experimental group and the control group in terms of diaper rash severity (p = 0.000; Wilcoxon test). This result indicates that the use of VCO can reduce the severity of diaper rash in infants aged 0-12 months. This study can be a reference for parents and health professionals in managing diaper rash in infants. Conclusion: Virgin Coconut Oil can be used as an alternative non-pharmacological management in reducing the severity of diaper rash in infants.Keywords: Diaper rash, Virgin Coconut Oil (VCO), infant, non-pharmacological management, alternative treatment